2019
DOI: 10.1111/srt.12755
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond laser treatment of atrophic and hypertrophic surgical scars: In vivo monitoring of results by means of 3D imaging and reflectance confocal microscopy

Abstract: Purpose A growing interest in the treatment of scars with picosecond laser (PSL) is evident, although the basis for scar improvement is poorly understood. The aim is to provide new insights into the role of PSL in scar improvement through noninvasive in vivo skin imaging. Methods A total of 16 patients with 20 surgical scars were treated with three sessions of PSL. Efficacy was estimated through blinded evaluations performed by external dermatologists, Vancouver Scar Scale (VSS), Global Assessment Improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 27 publications
6
44
1
1
Order By: Relevance
“…6,11 Picosecond lasers have been used for treating various types of scars with satisfactory clinical outcomes. 4,5,[12][13][14] In the present study, we demonstrated that stacking or nonstacking multiple-pulses of a focused picosecond laser at a wavelength of 1,064 generate large cystic or pseudocystic laser-induced tissue reactions in the epidermis and dermis. After dozens of stacking pulses of picosecond laser treatment, round to oval zones of tissue coagulation formed in the mid to lower dermis.…”
Section: Discussionsupporting
confidence: 50%
“…6,11 Picosecond lasers have been used for treating various types of scars with satisfactory clinical outcomes. 4,5,[12][13][14] In the present study, we demonstrated that stacking or nonstacking multiple-pulses of a focused picosecond laser at a wavelength of 1,064 generate large cystic or pseudocystic laser-induced tissue reactions in the epidermis and dermis. After dozens of stacking pulses of picosecond laser treatment, round to oval zones of tissue coagulation formed in the mid to lower dermis.…”
Section: Discussionsupporting
confidence: 50%
“…Picosecond laser for acne scars has been studied in one case series; four retrospective reviews; five prospective open-label clinical trials; and one randomized, split-face, comparison trial versus fractional 1550 nm erbium fiber laser involving a cumulative total of 194 subjects [8,9,63,65,66,71,72]. Additionally, there has been one case series of 16 patients studying picosecond laser treatment of hyperpigmented scars; one retrospective review of 24 patients with hypertrophic scars; one retrospective review of nine patients with atrophic surgical scars which was subsequently extended by the same group to include an additional eight subjects with atrophic scars and eight subjects with hypertrophic surgical scars; and one randomized, evaluator-blinded, split-body comparison trial of fractionated picosecond Nd:YAG laser versus 1565 nm fractional non-ablative laser for the treatment of striae alba in 20 subjects [64,[67][68][69][70].…”
Section: Scarsmentioning
confidence: 99%
“…Retrospective reviews of atrophic and hypertrophic surgical scar treatments with fractionated picosecond Nd:YAG laser have also demonstrated benefit. Interestingly, reflectance confocal microscopy of treated scars at the 6‐month time point post‐treatment revealed a net‐like reconfiguration of collagen fibers and a significant reduction of epidermal thickness in hypertrophic scars compared to baseline [69,70]. Once again, more robust studies are required to further evaluate these findings.…”
Section: Scarsmentioning
confidence: 99%
“…31 However, recent studies have also highlighted the effectiveness in the active stages of the disease. Depending on the wavelength, lasers act at different levels 32,33 ; in particular the infrared rays act on the sebaceous gland causing a thermal coagulation and consequently a reduced sebum production. 30 These include herbium glass and YAG laser.…”
Section: Lasermentioning
confidence: 99%